Evaluation of laryngoscopic view, intubation difficulty and sympathetic response during direct laryngoscopy in sniffing position versus simple head extension: a clinical comparative study - Chauhan, Sangeeta; Shende, Seema; Vinayak Shidhaye, Ramchandra (International Journal of Medical Research and Review, 2016)
Background: Proper position of the head and the neck is important for optimizing laryngoscopic view and for ease of endotracheal intubation.We compared two different positions, sniffing position and simple head extension during direct laryngoscopy on the basis of laryngoscopic view, intubation difficulty and sympathetic response. Methodology: One hundred twenty patients of age group 20-50 years, scheduled for elective surgeries under general anaesthesia were divided into two equal groups in a randomized fashion. In group A (n = 60), sniffing position during laryngoscopy and intubation; and in group B(n =60),simple head extension position during laryngoscopy and intubation. Laryngoscopy view, ease of intubation and hemodynamic parameters were recorded. Results: Demographic data and the different parameters for assessment of difficult airway were similar in both groups. Glottic visualization grade was superior in group A and intubation difficulty score were higher in Group B (P < 0.05), Hemodynamic parameters at different time intervals were comparable. Conclusion: Sniffing position during laryngoscopy was found to be superior to simple head extention position in respect of better glottis visualization and ease of intubation though no difference in sympathetic response to intubation was found.